Analysis of a Power Inverter Design Considering the Demand Characteristics of a House With Renewable Energy Sources - Selamogullari, Ugur S. (GAZI UNIV, 2020)
Increasing energy demand in the world has shifted the interest to renewable energy sources. Specifically, solar and wind power systems for both grid connected and stand-alone homes have become a widespread application. An inverter is used to obtain AC voltage with fixed amplitude and frequency in a renewable energy supplied residential house. When measured residential electrical power demand data is analyzed, it is seen that the demand varies within a wide range during a day and stays at low power levels most of the day. Thus, the light load efficiency of inverter circuit must be improved for residential applications. In this study, the effect of variable inductor use-with reference to the load current- at the inverter LC filter circuit on the inverter light load efficiency is investigated. It is shown that the inverter light load efficiency can be considerably improved due to the reduction of current ripple drawn from the inverter. With more efficient inverter design, the energy from renewable sources can be utilized more efficiently.
Keywords: Renewable energy; inverter design; residential electrical power demand; efficiency improvement; variable filter inductance; VARIABLE-INDUCTOR; Engineering